2011
DOI: 10.3164/jcbn.10-96
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effects of Mango (Mangifera indica L.) fruit on plasma ethanol level in a mouse model assessed with 1H-NMR based metabolic profiling

Abstract: The ameliorating effects of Mango (Mangifera indica L.) flesh and peel samples on plasma ethanol level were investigated using a mouse model. Mango fruit samples remarkably decreased mouse plasma ethanol levels and increased the activities of alcohol dehydrogenase and acetaldehyde dehydrogenase. The 1H-NMR-based metabolomic technique was employed to investigate the differences in metabolic profiles of mango fruits, and mouse plasma samples fed with mango fruit samples. The partial least squares-discriminate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Mango fruit intake provides antioxidants that may act in a synergistic way with other foods to offer protection [69]. Kim et al [70] confirmed that mango flesh and peel had ameliorating effects on plasma alcohol levels and increased the activities of ADH and ALDH in mice. A loading plot indicated that several compounds in mango fruit, such as fructose and aspartate, might enhance alcohol metabolism.…”
Section: Mangifera Indica Lmentioning
confidence: 71%
See 1 more Smart Citation
“…Mango fruit intake provides antioxidants that may act in a synergistic way with other foods to offer protection [69]. Kim et al [70] confirmed that mango flesh and peel had ameliorating effects on plasma alcohol levels and increased the activities of ADH and ALDH in mice. A loading plot indicated that several compounds in mango fruit, such as fructose and aspartate, might enhance alcohol metabolism.…”
Section: Mangifera Indica Lmentioning
confidence: 71%
“…Heteropolysaccharides Peduncle Mice Suppression of acute alcohol-induced liver injury through decreased serum levels of AST, ALT and liver MDA, and restored liver SOD, GST and GSH [63,64] Dihydromyricetin Rats Reduced alcohol consumption in an intermittent voluntary alcohol intake paradigm [65] Pyrus pyrifolia Polyphenols Fruit Humans Alleviation of alcohol hangover through lowered blood alcohol levels and modifed genetic variation of ALDH2 [67] Mice Alleviation of alcohol hangover through decreased blood alcohol levels [68] Mangifera indica L. Polyphenols Flesh and peel Mice Decreased plasma alcohol levels and increased activities of ADH and ALDH [70] Diospyros kaki Thunb.…”
Section: Hovenia Dulcismentioning
confidence: 99%
“…In experiments in which mango flesh or mango peel was administered to mice, followed by ethanol ingestion, blood ethanol levels were lower by more than 50% compared with the control group. This difference in ethanol concentration likely occurred due to the activation of ADH and cytosolic ALDH in the liver (238). The authors assumed that the effect observed could be mediated by fruc-tose and aspartate from the mango, which produce NAD ϩ and thus stimulate ADH and ALDH.…”
Section: G Food Modulating Activity Of Alcohol-metabolizing Enzymesmentioning
confidence: 99%
“…In the literature, Elaeagnus conferta was reported to increase the activity of ADH, and also had a high ratio of K/Na [ 18 ]. Mangifera indica and Durio zibethinus juices didn’t significantly affect the activities of ADH and ALDH in this study, while it was reported in the literature that Mangifera indica fruit could increase the activities of ADH and ALDH and Durio zibethinus fruit extracts inhibited yeast ALDH activity in vitro [ 12 , 31 ]. These differences could be because of different extracts containing different components, and in vitro study and in vivo study sometimes showing different results.…”
Section: Resultsmentioning
confidence: 58%